The level of safety awareness among the various types of construction workers in Johor Bahru - 331660 Radhlinah Kunju Ahmad; Universiti Teknologi Malaysia. Fakulti Alam Bina; Universiti Teknologi Malaysia. Pusat Pengurusan Penyelidikan (Skudai : Universiti Teknologi Malaysia, 2006)
PSZJBL